Ketahanan Digital dalam Transformasi Agribisnis (Studi pada Fenomena Penggunaan Facebook Marketplace oleh Petani Milenial Program YESS) - Yunandar, Detia Tri; Arsyad, Kisman Awaluddin; Nuryanti, Nuryanti; Ihsan, R. Muhammad; Parasdya, Sekar Diva (Universitas Gadjah Mada, 2025)
ABSTRACTThis study aims to analyze how Facebook Marketplace contributes to the digital resilience of millennial farmers in adapting to agribusiness transformation, particularly in terms of market access, digital literacy, and business innovation.This research employs a qualitative descriptive method with a phenomenological approach, collecting data through in-depth interviews and participatory observations. The interviews explore farmers' motivations, perceptions, and challenges in adopting this platform, while observations examine their interaction patterns with consumers. The findings indicate that Facebook Marketplace plays a significant role in strengthening the digital resilience of millennial farmers by expanding market networks, enhancing digital literacy, and fostering innovation in agribusiness strategies. However, challenges such as limited digital infrastructure and technological literacy gaps remain major obstacles. Therefore, this study highlights the importance of improving digital skills and strengthening infrastructure as key factors in the success of agribusiness digital transformation. The primary recommendation of this research is the implementation of continuous digital training programs for millennial farmers to optimize the use of digital platforms in agribusiness development.